2005
DOI: 10.1113/jphysiol.2005.095240
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous reflexes evoked during human walking are reduced when self‐induced

Abstract: Reflex responses are often less pronounced when they are self-induced, but this question has barely been investigated quantitatively. The issue is particularly relevant for locomotion since it has been shown that reflexes elicited during normal gait are important for the regulation of locomotion. The cortex is thought to be involved in the control of reflexes during gait, but it is unclear whether it plays a role in the modulation of these reflexes during the step cycle. During gait, weak electrical stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The electrical stimulus (a train of five rectangular pulses of 1 ms duration given at 200 Hz) was applied by a custom-made constant-current stimulator through a bipolar stimulation electrode (with poles of 0.5 cm and an interpole distance of 2.0 cm) that was positioned over the sural nerve (approximately halfway between the lateral malleolus and the Achilles tendon) of the most affected leg. For each subject the exact position of the stimulation electrode was determined according to the optimal irradiation to the lateral side of the foot (the innervation area of the sural nerve), similar to previously published methods (Baken et al 2006;Duysens et al 1996;Van Wezel et al 1997 and to those used by others (Yang and Stein 1990;Zehr et al 1998b).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The electrical stimulus (a train of five rectangular pulses of 1 ms duration given at 200 Hz) was applied by a custom-made constant-current stimulator through a bipolar stimulation electrode (with poles of 0.5 cm and an interpole distance of 2.0 cm) that was positioned over the sural nerve (approximately halfway between the lateral malleolus and the Achilles tendon) of the most affected leg. For each subject the exact position of the stimulation electrode was determined according to the optimal irradiation to the lateral side of the foot (the innervation area of the sural nerve), similar to previously published methods (Baken et al 2006;Duysens et al 1996;Van Wezel et al 1997 and to those used by others (Yang and Stein 1990;Zehr et al 1998b).…”
Section: Methodsmentioning
confidence: 99%
“…The same group participated as described in an earlier study (Nieuwenhuijzen et al 2006). The average age was 53 yr (SD 12; range, 42 to 73 yr).…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies have shown that during gait the cutaneous reflexes induce predominantly suppression in peroneus longus (Baken et al, 2006) but these experiments were performed on healthy subjects. It would be of great interest to see if these suppressions are more pronounced on the injured side in subjects with FAI during gait.…”
Section: Cutaneous Reflexes In Chronic Ankle Instabilitymentioning
confidence: 99%